Analisis Peningkatan Total Asset Pada Unit Usaha Syariah Di Indonesia - Dina Zulfa Ofera (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2019)
In Indonesia, economic fluctuations continue to occur every year. Where in thesefluctuations, a large impact on the economic sector, both the trading system andfinancial institutions. In this case, Islamic financial institutions continue to showtheir existence in Indonesia, as if they were not affected by these economicfluctuations. Therefore, in this paper I want to explain and show the existence ofIslamic financial institutions, which are seen from the total assets of shariabusiness units in Indonesia. The purpose of the research carried out, shows ordescribes the total assets owned by the Islamic business unit. This research usesqualitative research methods, where researchers only describe the documentspublished by Bank Indonesia, and the Financial Services Authority.